2020
DOI: 10.1155/2020/2528676
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Risk Factors of Active Tuberculosis in Patients with Behçet’s Disease

Abstract: To investigate the clinical features and potential risk factors of active tuberculosis (ATB) in Behçet’s disease (BD), we conducted a case-control study on hospitalized BD patients in our institute from 2010 to 2019. BD patients with ATB were enrolled as the case group. The control group was selected by random number sampling from the remaining BD patients, including those with latent tuberculosis infection, previous tuberculosis, or without tuberculosis. Finally, we reviewed 386 BD patients and identified 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Few studies reported the prevalence of ATB in patients with BD. Our previous study showed that 5.4% of the hospitalized patients with BD were diagnosed with ATB[ 24 ]. Similarly, the prevalence of ATB in hospitalized patients with BD was higher than that obtained in this epidemiological survey (2251/100,000).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies reported the prevalence of ATB in patients with BD. Our previous study showed that 5.4% of the hospitalized patients with BD were diagnosed with ATB[ 24 ]. Similarly, the prevalence of ATB in hospitalized patients with BD was higher than that obtained in this epidemiological survey (2251/100,000).…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently observed in patients along the Silk Road in Asia and Central Asia. [ 8 ] Mycobacterium tuberculosis is known to trigger Behçet's disease. [ 9 ] Moreover, the incidence of TB infection in Behçet's disease sufferers increases significantly, due to both cell-mediated immune system disorders observed in these patients, and the medications used in the treatment of this disease that suppress the immune system, in particular, anti- TNF agents.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Moreover, the incidence of TB infection in Behçet's disease sufferers increases significantly, due to both cell-mediated immune system disorders observed in these patients, and the medications used in the treatment of this disease that suppress the immune system, in particular, anti- TNF agents. [ 8 ] Consequently, TB infection in Behçet's disease sufferers can be both the cause and the result. In the present case, however, the patient was not using anti-TNF agents and TB infection developed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent study by Shen et al, BD patients with latent Mycobacterium infection were shown to have worse clinical outcomes, with more severe dermatological and ophthalmological damage [20]. Moreover, BD patients with active TB seem more prone to having systemic symptoms, including fever and weight loss, arthritis, and thrombotic events [23].…”
Section: Relationship Between Behçet Disease and Tuberculosismentioning
confidence: 99%